Pembentukan Religiusitas Remaja Muslim: Tinjauan Deskriptif Analitis - Warsiyah, Warsiyah (IAIN Ponorogo, 2018)
The study of the factors that shape the religiosity of Muslim youth is important given the many cases of deviant behavior reported both through mass media and research results involving Muslim youth. This is because religiosity has an important role in human self-control because it can affect attitudes, perceptions, emotions and even on their behavior. This paper is an analytical study of various related literature sources on factors that can shape the religiosity of Muslim youth. The discussion begins with a study of the definition and dimensions of Muslim religiosity, the development of the religious psyche in humans, the factors that shape adolescent religiosity. The results of the discussion show that the dominant factors of shaping the religiosity of Muslim adolescents are the religious behavior of parents, Islamic religious education in school, and peer conformity.ØªØ¹ØªØ¨Ø± Ø¯Ø±Ø§Ø³Ø© Ø§ÙØ¹ÙØ§Ù Ù Ø¹Ù ØªØ¯ÙÙÙ Ø§ÙØ´Ø¨Ø§Ø¨ Ø§ÙÙ Ø³ÙÙ Ù ÙÙ Ø© Ø¨Ø§ÙÙØ¸Ø± Ø¥ÙÙ ÙØ«Ø±Ø© Ø§ÙØ³ÙÙÙ Ø§ÙÙ ÙØØ±Ù Ø§ÙØ°Ù ÙØ¸ÙØ± Ù Ù Ø®ÙØ§Ù ÙØ³Ø§Ø¦Ù Ø§ÙØ¥Ø¹ÙØ§Ù ÙÙØªØ§Ø¦Ø¬ Ø§ÙØ£Ø¨ØØ§Ø« Ø§ÙØªÙ ÙØ´Ø§Ø±Ù ÙÙÙØ§ Ø§ÙØ´Ø¨Ø§Ø¨ Ø§ÙÙ Ø³ÙÙ . ÙØ°Ø§ ÙØ£Ù Ø§ÙØªØ¯ÙÙ ÙÙ Ø¯ÙØ± Ù ÙÙ ÙÙ Ø¶Ø¨Ø· Ø§ÙÙÙØ³ Ø§ÙØ¨Ø´Ø±Ù ÙØ£ÙÙ ÙÙ ÙÙ Ø£Ù ÙØ¤Ø«Ø± Ø¹ÙÙÙÙ ÙÙ Ø§ÙÙ ÙØ§ÙÙ ÙØ§ÙØªØµÙØ±Ø§Øª ÙØ§ÙØ¹ÙØ§Ø·Ù ÙØ§ÙØ³ÙÙÙÙØ§Øª. ÙØ°Ù Ø§ÙÙØ±ÙØ© ÙÙ Ø¯Ø±Ø§Ø³Ø© ØªØÙÙÙÙØ© ÙÙÙ ØµØ§Ø¯Ø± ÙØ§ÙÙ Ø±Ø§Ø¬Ø¹ Ø§ÙÙ Ø®ØªÙÙØ© Ø°Ø§Øª Ø§ÙØµÙØ© ÙÙØ¹ÙØ§Ù Ù Ø§ÙØªÙ ÙÙ ÙÙ Ø£Ù ØªÙÙÙÙÙ ØªØ¯ÙÙÙ Ø§ÙØ´Ø¨Ø§Ø¨ Ø§ÙÙ Ø³ÙÙ . ØªØ¨Ø¯Ø£ Ø§ÙÙ ÙØ§ÙØ´Ø© Ø¨Ø¯Ø±Ø§Ø³Ø© Ø¹Ù ØªØ¹Ø±ÙÙ ÙØ£Ø¨Ø¹Ø§Ø¯ ØªØ¯ÙÙ Ø§ÙÙ Ø³ÙÙ Ø ÙØªØ·ÙØ± Ø§ÙÙÙØ³ Ø§ÙØ¯ÙÙÙØ© ÙØ¯Ù Ø§ÙØ¨Ø´Ø ÙØ§ÙØ¹ÙØ§Ù Ù Ø§ÙØªÙ ØªÙÙÙÙÙ ØªØ¯ÙÙ Ø§ÙÙ Ø±Ø§ÙÙÙÙ. ÙØªØ¸ÙØ± ÙØªØ§Ø¦Ø¬ Ø§ÙÙ ÙØ§ÙØ´Ø© Ø£Ù Ø§ÙØ¹ÙØ§Ù Ù Ø§ÙÙ Ø¤Ø«Ø±Ø© ÙÙ ØªÙÙÙÙ ØªØ¯ÙÙ Ø´Ø¨Ø§Ø¨ Ø§ÙÙ Ø³ÙÙ ÙÙ ÙÙ Ø§ÙØ³ÙÙÙ Ø§ÙØ¯ÙÙÙ ÙÙØ¢Ø¨Ø§Ø¡Ø ÙØ§ÙØªØ±Ø¨ÙØ© Ø§ÙØ¯ÙÙÙØ© Ø§ÙØ¥Ø³ÙØ§Ù ÙØ© ÙÙ Ø§ÙÙ Ø¯Ø±Ø³Ø©Ø ÙÙ Ø·Ø§Ø¨ÙØ© Ø§ÙØ²Ù ÙØ§Ø¡.